2015
DOI: 10.14814/phy2.12552
|View full text |Cite
|
Sign up to set email alerts
|

High levels of isotope elimination improve precision and allow individual-based measurements of metabolic rates in animals using the doubly labeled water method

Abstract: Doubly labeled water (DLW) can be used to measure energy expenditure in free-ranging animals, but questions have been raised about its accuracy in different species or contexts. We investigated whether differences in the extent of isotope elimination affects the precision and accuracy of the DLW method, which can vary according to the experimental design or metabolic rate of the species. Estimated total energy expenditure by the DLW method (TEEdlw) was compared with actual total energy expenditure simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…The method allowed an estimation of initial isotope enrichment from a single blood sample and was a less invasive technique with lower impact on the behavior of study subjects ( Schultner et al, 2010 ; Niizuma & Shirai, 2015 ). Recent validation studies have demonstrated that the precision of the DLW technique can be increased by using a longer sampling interval and/or by applying it to a species with a higher metabolic rate ( Shirai et al, 2015 ; Kume et al, 2019 ). The DLW injectate used in our study contained 21.0 atom percent 18 O, 10.5 atom percent 2 H, and 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method allowed an estimation of initial isotope enrichment from a single blood sample and was a less invasive technique with lower impact on the behavior of study subjects ( Schultner et al, 2010 ; Niizuma & Shirai, 2015 ). Recent validation studies have demonstrated that the precision of the DLW technique can be increased by using a longer sampling interval and/or by applying it to a species with a higher metabolic rate ( Shirai et al, 2015 ; Kume et al, 2019 ). The DLW injectate used in our study contained 21.0 atom percent 18 O, 10.5 atom percent 2 H, and 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…We diluted the serum and injectate samples with distilled water measured with an electronic balance (Mettler-Toledo, Columbus, OH, USA) to the nearest 0.01 mg. We analyzed the 2 H and 18 O isotope concentrations of the serum, DLW injectate, and distilled water using isotope ratio mass spectrometry (IRMS; Hydra 20-20, Sercon, Crewe, UK; Shirai et al, 2012 ; Shirai et al, 2015 ). We used the water equilibration method ( Horita et al, 1989 ) to analyze the serum, DLW injectate, and distilled water in duplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fieldwork was permitted by the Ministry of the Environment (21-26-0291 0292, 21-27-0367 0368 0369 0370 0371, 21-28-0344 035 036 037) and the Agency of Cultural Affairs (26-4-2188, 27-4-1928, 29-4-18). Measurements of resting metabolic rate using respirometry in air and on water Oxygen consumption rate (Vo 2 ) was measured using an open-flow respirometry system composed of an acrylic metabolic chamber and an oxygen analyzer (Xentra 4100, Servomex Ltd, UK) as previously described in Shirai et al (2015). For the measurement of RMR in air, a 20-L metabolic chamber (20 cm long × 25 cm high × 40 cm wide) was submerged in a thermostatic water bath and maintained at 4.7-20.7℃.…”
Section: Study Area and Speciesmentioning
confidence: 99%
“…The method allowed an estimation of initial isotope enrichment from a single blood sample and was a less invasive technique with lower impact on the behavior of study subjects (Schultner et al, 2010;. Recent validation studies have demonstrated that the precision of the DLW technique can be increased by using a longer sampling interval and/or by applying it to a species with a higher metabolic rate (Shirai et al, 2015;Kume et al, 2019). The DLW injectate used in our study contained 21.0 atom percent 18 O, 10.5 atom percent 2 H, and 0.9% NaCl.…”
Section: Study Area and Speciesmentioning
confidence: 99%